Mating in the pseudogamic apomictic Anemopaegma acutifolium DC: Another case of pseudo-self-compatibility in Bignoniaceae? - Sampaio, D. S.; Bittencourt, N. S. [UNESP]; Oliveira, P. E. (Wiley, 2013)
Self-compatibility in apomictic pseudogamic species is considered fundamental to assure reproduction by seeds in extreme situations, making apomictic species more advantageous than sexual ones in these scenarios. Anemopaegma acutifolium is a polyploidy, apomictic sporophytic species with no endosperm development in ovules of unpollinated pistils, which indicates obligate pseudogamy. Thus, the aim of the present work is to study the breeding system and post-pollination events to test if there is similar pseudogamous development irrespective of pollination treatment. We analysed fruit and seed set obtained in controlled experimental pollinations, as well as embryo number per seed, and the progress of ovule penetration, fertilisation and early endosperm development between self- and cross-pollinated pistils. We found that the species is self-fertile and that spontaneous selfing fruit set is also possible, although emasculated flowers never form fruits. Selfed pistils were as efficient as crossed ones for all parameters analysed, except for a delay in endosperm development observed in the former that may be an effect of the late-acting self-incompatibility. Therefore, the avoidance of selfed pistil abortion seems to be promoted by the presence of adventitious embryos and a normal endosperm. We conclude that A. acutifolium shows apomixis-related pseudo-self-compatibility, as in other self-fertile apomictic species of Bignoniaceae, which confer reproductive assurance and increases fruit-set and persistence ability in fast-changing tropical habitats. © 2012 German Botanical Society and The Royal Botanical Society of the Netherlands.
Keywords: Polyembryony; Polyploidy; Pseudogamy; Self-fertility; Sporophytic apomixis